Genetic characterization of Gac (Momordica cochinchinesis) accessions in Southern Vietnam by ISSR markers - VIET THE HO; HUU TRIET LE; THANH AN NGUYEN (Biodiversitas Journal of Biological Diversity, 2019)
Ho VT, Le HT, Nguyen TA. 2019. Genetic characterization of Gac (Momordica cochinchinesis) accessions in Southern Vietnam by ISSR markers. Biodiversitas 20: 387-392. Gac (Momordica cochinchinesis) plays important roles in Vietnamese cuisine and medicine. It has high nutrient and medicinal values. Demand of gac fruit as ingredient for food processing and raw material for health industry requires accelerated gac cultivation. However, gac quality is variable due to the uncertain available germplasm and its management as breeding stock. Identification of gac cultivars and landraces in Vietnam is mainly based on personal experience relying on morphological traits, thus the conservation and breeding have low impact on productivity and quality of product. Recently, the development of molecular markers has been useful in identifying specific plant(s). In this study, genetic richness and relativeness of 14 gac accessions collected from different provinces in Southern Vietnam were evaluated by using 10 Inter-Simple Sequence Repeats (ISSR) markers. Results revealed large variation in genetic background of studied gac accessions. Seven DNA-based markers with potential to differentiate gac genotypes were recorded. The results provide molecular biological information for classification, identification plant origins, breeding and conserving programs of gac in Vietnam.